TRANSFORMASI DIGITAL : APLIKASI CANVA SEBAGAI MEDIA PEMBELAJARAN YANG INOVATIF DAN KOLABORATIF DALAM PENDIDIKAN SD/MI - Saputra, Mohammad Irvan Bayu; Rohman, Muhammad Abdur (Abtadi : Jurnal Pendidikan Dasar, 2024)
ABSTRACT The digital transformation has brought comprehensive changes across variousdomains, one of which is the realm of education. One digital innovation that can be utilized inteaching is the Canva application, a graphic design system offering various features and templates that are use friendly for creating various type visual learning materialsto create different types of visual materials.The use of Canva in elementary (SD) and Islamic elementary schools (MI) can serve as an innovative and collaborative medium, thus enhancing the quality of education. The objective of this research is to explore the implementation of Canva in learning media in SD/MI and analyze its impact on student engagement an learning outcomes. Literature review is the method employd in this study, with the integration of Canva into the curriculum, aiming to create a more dynamic and enjoyable learning environment.